A convenient synthesis of gimeracil. (1st January 2018) - Li, Xiao-Lin; Zhu, Hao-Ting; Zhan, Li; Liu, Ting; Cheng, Guang; Liu, Ning; Yu, Shan-Bao; Li, Hui; Luo, Yu; Yang, Fan; Tang, Jie
A practical three-step synthetic approach to gimeracil in a 68% overall yield is described, using 2, 4-dimethoxypyridine as the starting material with 3, 5-dichloro-2, 4-dimethoxypyridine and 3, 5-dichloro-2, 4-dihydroxypyridine as intermediates. The advantages of this procedure include short reaction steps, simple operation and good yield.